Composite Polylactic-Methacrylic Acid Copolymer Nanoparticles for the Delivery of Methotrexate. (5th July 2012) - Sibeko, Bongani; Choonara, Yahya E.; du Toit, Lisa C.; Modi, Girish; Naidoo, Dinesh; Khan, Riaz A.; Kumar, Pradeep; Ndesendo, Valence M. K.; Iyuke, Sunny E.; Pillay, Viness
Abstract : The purpose of this study was to develop poly(lactic acid)-methacrylic acid copolymeric nanoparticles with the potential to serve as nanocarrier systems for methotrexate (MTX) used in the chemotherapy of primary central nervous system lymphoma (PCNSL). Nanoparticles were prepared by a double emulsion solvent evaporation technique employing a 3-Factor Box-Behnken experimental design strategy. Analysis of particle size, absolute zeta potential, polydispersity (Pdl), morphology, drug-loading capacity (DLC), structural transitions through FTIR spectroscopy, and drug release kinetics was undertaken. Molecular modelling elucidated the mechanisms of the experimental findings. Nanoparticles with particle sizes ranging from 211.0 to 378.3 nm and a recovery range of 36.8–86.2 mg (Pdl ≤ 0.5 ) were synthesized. DLC values were initially low (12 ± 0.5 %) but were finally optimized to 98 ± 0.3 %. FTIR studies elucidated the comixing of MTX within the nanoparticles. An initial burst release (50% of MTX released in 24 hours) was obtained which was followed by a prolonged release phase of MTX over 84 hours. SEM images revealed near-spherical nanoparticles, while TEM micrographs revealed the presence of MTX within the nanoparticles. Stable nanoparticles were formed as corroborated by the chemometric modelling studies undertaken.